TYPE 1 DIABETES IN TRANSFUSION-DEPENDENT BETA-THALASSEMIA MAJOR A CASE SERIES - Nanda, Bikash Chandra; Majhi, Dr. Chakradhar; Hati, Dr. Tuhin (Student's Journal of Health Research Africa, 2024)
Background Regular blood transfusions, essential for managing transfusion-dependent beta-thalassemia major (TDT), frequently lead to iron overload, which can harm multiple organs, including the pancreas. Iron deposition in pancreatic beta-cells may result in Type 1 Diabetes Mellitus (T1DM). This case series examines the clinical characteristics, diagnostic findings, and management strategies for ten adult TDT patients who developed T1DM due to iron overload. Methods This study included 10 adult patients, aged between 18 and 35 years, presenting with TDT. Data collected encompassed fasting plasma glucose (FPG), HbA1c, serum ferritin levels, and chelation therapy adherence. All patients required chronic transfusion therapy and exhibited varying levels of compliance with iron chelation protocols. Results In this case series, ten patients with transfusion-dependent beta-thalassemia major (TDT) exhibited ferritin levels ranging from 2,600 to over 4,000 ng/mL and HbA1c levels between 6.5% and 9.2%, reflecting varying glycemic control. All patients had elevated fasting plasma glucose (FPG) levels, ranging from 110 to 200 mg/dL. Chelation therapy compliance was generally poor or suboptimal, influencing clinical outcomes. While most patients showed improvement or stabilization after treatment, one patient had limited improvement due to advanced disease complications. Conclusion Proactive monitoring for glucose abnormalities and rigorous adherence to iron chelation are essential to mitigate diabetes onset in TDT patients. Regular oral glucose tolerance tests (OGTT) and comprehensive care are recommended to address this high-risk population effectively. Recommendation Further research is needed to refine screening protocols and explore novel therapeutic approaches to prevent iron-induced diabetes.